Optimalisasi Metode Pembelajaran Bernyanyi untuk Menumbuhkan Perkembangan Kognitif Anak TK Dharmawanita Krajan Kesugihan Pulung Ponorogo - Siti Amaliyah; Dyan Putri Ayu (Social Science Academic, 2025)
The singing method used by tea chers in early childhood in learning activities is fun so that children can more easily remember learning material. The service was carried out at Kindergarten Dharmawanita Krajan Kesugihan Pulung Ponorogo which aims to determine the increase in cognitive abilities in early childhood through the singing method. And also use the mentoring service method. Based on the results of the study, it was shown that the singing method played an important role in the cognitive abilities of children at Kindergarten Dharmawanita Krajan Kesugihan Pulung Ponorogo.